Investigação por primeiros princípios da dopagem em materiais bidimensionais de rede hexagonal: monocamadas de grafeno, nitreto de boro e dissulfeto de molibdênio - Regiane do Nascimento (2015)
Chemical doping is a well-known method used to modify the electronicproperties of materials. Using ab initio density functional theory calculations, we have investigated the effect of graphene co-doped with boron and nitrogen atoms at low concentration. The results for the eletronic structure of doped graphene indicate that the B atoms have a largerhybridization with graphene atoms than the N atoms. The theoretical signatures of substitutional dopants are evident at the C K-edge spectra from the X-ray absorption of graphene co-doped. In the interface of these materials the C-B bonds, of Klein extended type are more stable than the C-N bonds. The band structureccalculations predict that co-doped graphene band gaps can vary over an order of magnitude, for the same BN cconcentration, dependingcon the system morphology. This result was described by a tight-binding model. It was showncthat the band gap size is affected by the lattice deformation.Through Atomic Force Microscopy (AFM) measurements the formation of self-assembledmonolayers - SAMs of OPA (Octadecyl phosphonic Acid) atop graphene, boron nitride and molybdenum disulde was observed. Our theoretical results for the energetic stability of these systems are in agreement with the experimental results, indicating that these acids form 2D crystals, with the alkyl chain aligned to substrate zigzag direction. Also, it was observed an induced charge density due to OPA adsorption on all substrates. The theoretical model of SAMs formed by OPA was able to identify that the wrinkles in h-BN substrates are crystallographically oriented along the armchair direction. Together with AFM image, thismodel of SMAs atop the MoS2 have also evidenced grain boundaries in the substrate.